Region Complex Distinctions of Class, Gender and Race in Tite Poulitte by George Washington Cable and The Convent Girl by Grace King - yustin sartika (Universitas Aki, 2015)
Writers, female and male, black and white all wrote about the hardship of being the culture that wasn’t liked. Regional writers emphasized characteristics of specific geographic settings—the culture, speech (dialect), customs, and landscape. As they recorded and commented on the distinctive culture, speech and customs that distinguished specific geographical areas, these authors also struggled with the role of class, race and gender in local life. Keywords: regional writers, class, race, gender